The acute light-induction of sleep is mediated by OPN4-based photoreception. - Lupi, D; Oster, H; Thompson, S; Foster, R (2008)
Sleep is regulated by both homeostatic and circadian mechanisms. The latter, termed 'process c', helps synchronize sleep-wake patterns to the appropriate time of the day. However, in the absence of a circadian clock, overall sleep-wake rhythmicity is preserved and remains synchronized to the external light-dark cycle, indicating that there is an additional, clock-independent photic input to sleep. We found that the direct photic regulation of sleep in mice is predominantly mediated by melanopsin (OPN4)-based photoreception of photosensitive retinal ganglion cells (pRGCs). Moreover, OPN4-dependent sleep regulation was correlated with the activation of sleep-promoting neurons in the ventrolateral preoptic area and the superior colliculus. Collectively, our findings describe a previously unknown pathway in sleep regulation and identify the pRGC/OPN4 signaling system as a potentially new pharmacological target for the selective manipulation of sleep and arousal states.